Superstition as an Impediment to the Education of Commercial Fishermen: A Psychocultural Investigation Using Video - Roger Boshier (Adult Education Research Conference, 1999)
Commercial fishermen are prone to be superstitious and engage in rituals of avoidance designed to resolve anxiety and "diminish" danger. Video interviews with British Columbia fishermen illuminate this problem. The author pleads for a broadening of techno-rational approaches to prevention-education. Psycho-cultural, as well as techno-rational factors (equipment etc) should be considered.